The illusion of invariant quantities in life histories. - Nee, S; Colegrave, N; West, SA; Grafen, A (2005)
Life-history theory attempts to provide evolutionary explanations for variations in the ways in which animal species live their lives. Recent analyses have suggested that the dimensionless ratios of several key life-history parameters are the same for different species, even across distant taxa. However, we show here that previous analyses may have given a false picture and created an illusion of invariants, which do not necessarily exist; essentially, this is because life-history variables have been regressed against themselves. The following question arises from our analysis: How do we identify an invariant?